2019
DOI: 10.4132/jptm.2019.06.07
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characterization and Prognostic Implication of SMAD4 Expression in Colorectal Carcinoma

Abstract: Background: SMAD family member 4 (SMAD4) has gained attention as a promising prognostic factor of colorectal cancer (CRC) as well as a key molecule to understand the tumorigenesis and progression of CRC. Methods: We retrospectively analyzed 1,281 CRC cases immunohistochemically for their expression status of SMAD4, and correlated this status with clinicopathologic and molecular features of CRCs. Results: A loss of nuclear SMAD4 was significantly associated with frequent lymphovascular and perineural invasion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The number of differently sized repeats involving mononucleotide microsatellite loci was counted and MSI status was deemed positive (MSI‐high) when the fraction of unstable microsatellite loci over the total examined loci was higher than 20%. Conventional MSI testing was performed based on polymerase chain reaction (PCR) using the allele profiles of five microsatellite markers (BAT‐26, BAT‐25, D5S346, D17S250, and S2S123), as described previously [28]; the two tests gave concordant results in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…The number of differently sized repeats involving mononucleotide microsatellite loci was counted and MSI status was deemed positive (MSI‐high) when the fraction of unstable microsatellite loci over the total examined loci was higher than 20%. Conventional MSI testing was performed based on polymerase chain reaction (PCR) using the allele profiles of five microsatellite markers (BAT‐26, BAT‐25, D5S346, D17S250, and S2S123), as described previously [28]; the two tests gave concordant results in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, four studies had evaluated the prognostic value for RFS [ 47 , 81 , 88 , 101 ]. Six studies included cancer-specific survival [ 26 , 46 , 48 , 65 , 98 , 103 ], whereas three reported progression-free survival (PFS) [ 32 , 76 , 84 ]. All others reported either OS and/or DFS.…”
Section: Resultsmentioning
confidence: 99%
“…SMAD4 is a tumor suppressor gene that regulates cell proliferation, distinction, and extracellular matrix production [ 39 ]. It has been reported that SMAD4 acts as a prognostic biomarker in various human malignancies such as colorectal carcinoma [ 40 ] and pancreatic carcinoma [ 41 ], but its role as a prognostic marker in breast carcinoma is still unclear [ 42 ]. Deckers et al [ 43 ] informed that SMAD4/TGF-β-induced growth protection and apoptosis only happened at early stages of BC.…”
Section: Discussionmentioning
confidence: 99%